A facile synthesis of boron nitride supported zinc cobalt sulfide nano hybrid as high-performance pseudocapacitive electrode material for asymmetric supercapacitors. (December 2020) - Maity, Chandan Kumar; Goswami, Nilanjana; Verma, Kartikey; Sahoo, Sumanta; Nayak, Ganesh Chandra
Highlights: Template-free synthesis of quaternary nanohybrid based on zinc cobalt sulphide, BN, CNT, polypyrrole. Tuning behaviour of BN in electrochemical activity. Capacitance retention of 106% after 10, 000 cycles for quaternary nanohybrid. Asymmetric supercapacitor device exhibited maximum specific energy of 49.6 Wh/kg. Abstract: High specific energy, extended working potential, and elevated cyclic stability are the major issues regarding supercapacitor technology. To fabricate a competent hybrid supercapacitor electrode, it is necessary to combine both pseudocapacitive and electric double-layer capacitor (EDLC)-type materials smartly. The prime objective of this work is to develop a high-performance asymmetric supercapacitor (ASC) device with long-term cycling stability and extended working potential. Accordingly, an ASC device was fabricated by using sphere-like pseudocapacitive Zinc Cobalt sulfide (ZCS) in combination with other pseudocapacitive [Boron Nitride (BN) and Polypyrrole (PPY)] and EDLC-type [CNT] materials. The synthesized quaternary composite exhibited maximum specific capacitance (Csc ) of 534 and 785 F/g in aqueous (1 M KCl) and organic [(1 M TEABF4 in acetonitrile (ACN)] electrolytes, respectively. Moreover, it also exhibited excellent cycling stability (capacitance retention of 106% after 10, 000 charge/discharge cycles) in aqueous electrolyte. Apart from this, a theoretical study has been exposed to determine the EDLC and pseudocapacitive contribution of the electrode materials. Further, the ASC device exhibited an extended working potential (worked up to 1.8 V) with high specific energy of 49.6 Wh/kg in organic electrolyte. With these promising electrochemical performance, this mixed metal chalcogenide based ASC is considered as potential candidate for next-generation supercapacitors. Graphical abstract: Image, graphical abstract